2021
DOI: 10.2196/24202
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Apps for Foot Measurement in Pedorthic Practice: Scoping Review

Abstract: Background As the use of smartphones increases globally across various fields of research and technology, significant contributions to the sectors related to health, specifically foot health, can be observed. Numerous smartphone apps are now being used for providing accurate information about various foot-related properties. Corresponding to this abundance of foot scanning and measuring apps available in app stores, there is a need for evaluating these apps, as limited information regarding their e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…We have performed an electronic search to identify the relevant apps from three major commercial app stores, i.e., Google Play Store, Apple App Store, and Microsoft Store. Following similar approaches used in previous studies (Rivera et al, 2016;Kabir et al, 2021), a keyword-based search process was used. The guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) (Tricco et al, 2018) were followed to ensure transparency and clarity in reporting, as well as the ability for other researchers to replicate the search process.…”
Section: App Search Proceduresmentioning
confidence: 99%
“…We have performed an electronic search to identify the relevant apps from three major commercial app stores, i.e., Google Play Store, Apple App Store, and Microsoft Store. Following similar approaches used in previous studies (Rivera et al, 2016;Kabir et al, 2021), a keyword-based search process was used. The guidelines for Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) (Tricco et al, 2018) were followed to ensure transparency and clarity in reporting, as well as the ability for other researchers to replicate the search process.…”
Section: App Search Proceduresmentioning
confidence: 99%
“…To learn significant criteria and standards for evaluating the usefulness of mobile apps, an extensive review of existing mobile app rating scales was conducted. After analyzing the existing app rating scales [20,21,22,23,24], we concluded that each of them is suited for distinct categories of apps. We focused on essential software quality attributes such as usability, reliability, functionality, and performance & efficiency after analyzing existing researches on software quality evaluation.…”
Section: Csa Apps Rating Scalementioning
confidence: 99%
“…As this is a very sensitive and extremely important issue, we wanted to make sure that the app rating scale we develop is suitable for assessing this category of apps. For this, we took insight from the existing rating scales such as the mobile app rating scale (MARS) [25], end-user version of the MARS (uMARS) [26], and app rating scale for foot measurement apps (FootMARS) [24], and modified these for suiting the required evaluation of CSA education apps. We especially adopted distinctive categorical regions from the FootMARS rating scale [24] and introduced an extended variant of the mobile app rating scale for rating CSA education apps.…”
Section: Csa Apps Rating Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Approaches based on photogrammetry [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] in most cases use 2D images as input to generate a 3D model. The big advantage of photogrammetry is that the input data can be generated easily and cheaply without the need for special hardware.…”
Section: Introductionmentioning
confidence: 99%